The appropriateness of the macroeconomic imbalance procedure for Central and Eastern European Countries - Geraldine Dany-Knedlik; Martina Kämpfe; Tobias Knedlik (Empirica, 2021)
The European Commission's Scoreboard of Macroeconomic Imbalances is a rare case of a publicly released early warning system. It was published first time in 2012 by the European Commission as a reaction to public debt crises in Europe. So far, the Macroeconomic Imbalance Procedure takes a one-size-fits-all approach with regard to the identification of thresholds. The experience of Central and Eastern European Countries during the global financial crisis and in the resulting public debt crises has been largely different from that of other European countries. This paper looks at the appropriateness of scoreboard of the Macroeconomic Imbalances Procedure of the European Commission for this group of catching-up countries. It is shown that while some of the indicators of the scoreboard are helpful to predict crises in the region, thresholds are in most cases set too narrow since it largely disregarded the specifics of catching-up economies, in particular higher and more volatile growth rates of various macroeconomic variables.
Keywords: 330; Macroeconomic Imbalances Procedure (MIP); Scoreboard; Central and Eastern European Countries (CEEC); Early warning system; Signals approach; Probid method